16. Prevalence of knowledge and attitude about secondhand smoke among pregnant women attending antenatal care at Central Women’s hospital in Myanmar - Nyi Maung, Hein; Thet Aung, Kyaw; Maung Maung, Thae; Pyae Phyo, Aung; Hnin Pwint, Khin; Moe Aye, Moe; Hanh, Nguyen Thi Thuy (Tạp chí Nghiên cứu Y học, 2022)
Public health experts are aware of secondhand smoke (SHS) dangers, particularly for vulnerable groups like pregnant women. This study aims to describe the prevalence of SHS among pregnant women, including their knowledge, and attitude towards SHS. This study was a cross-sectional descriptive study conducted at Central Women’s Hospital in the Yangon Region, Myanmar in 2022. Out of 407 participants, the prevalence of SHS exposure was 65.4%. The participants have higher levels of knowledge (74%) and attitude (87%) about SHS. Knowledge level was negatively associated with SHS exposure at home. The findings highlight the need for community guidance programs, policies, and interventions to establish smoke-free environments. It is also important to conduct behavioral interventions.